2016
DOI: 10.1167/iovs.15-18235
|View full text |Cite
|
Sign up to set email alerts
|

Cone Viability Is Affected by Disruption of Melatonin Receptors Signaling

Abstract: PurposePrevious studies have demonstrated that melatonin has an important role in the modulation of photoreceptor viability during aging and may be involved in the pathogenesis of age-related macular degeneration.This hormone exerts its influence by binding to G-protein coupled receptors named melatonin receptor 1 (MT1) and 2 (MT2). Melatonin receptors 1 and 2 activate a wide variety of signaling pathways.MethodsMelatonin-proficient mice (C3H/f+/+) and melatonin-proficient mice lacking MT1 or MT2 receptors (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
(66 reference statements)
1
35
0
1
Order By: Relevance
“…Finally, it is worth noting that disruption of the retinal melatonin system (a key circadian output in the eye) also produces a significant reduction in the number of cone photoreceptors (about 30%) during aging (25). Hence, it appears that a significant feature of the dysfunction of the retinal circadian system produced by genetic mutation of the clock genes or its circadian output is the effect on cone viability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that disruption of the retinal melatonin system (a key circadian output in the eye) also produces a significant reduction in the number of cone photoreceptors (about 30%) during aging (25). Hence, it appears that a significant feature of the dysfunction of the retinal circadian system produced by genetic mutation of the clock genes or its circadian output is the effect on cone viability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has long been known that the corneal epithelium exhibits high amplitude rhythms of mitotic activity (Scheving & Pauly, 1974, Scheving et al, 1974) that are likely controlled locally. The same can be said for the ciliary body and the findings that intraocular pressure, aqueous humor flow, and aqueous cAMP levels all exhibit circadian rhythms (Boyd & McLeod, 1964, Rowland et al, 1986, Smith & Gregory, 1989) that are regulated through a noradrenergic system (Eakins & Eakins, 1964, Gianesini et al, 2016, Yoshitomi & Gregory, 1991). It is possible for example, that such regulation involves synchronization of a local clock in the ciliary body that in turn regulates secretion of aqueous humor.…”
Section: Multiple Ocular Clocksmentioning
confidence: 90%
“…In addition, melatonin, which is normally high at night, potentiates light damage (Wiechmann & O'Steen, 1992) and its antagonist, luzindole, is neuroprotective for photoreceptors (Sugawara et al, 1998). Furthermore, loss of both the MT1 and MT2 melatonin receptors ( MTNR1A and MTNR1B ) results in attrition of cones in older mice (Gianesini et al, 2016). In contrast to its impact on photoreceptors, melatonin and its type 1 receptor ( MT1, MTNR1A ) are important in maintaining ganglion cells as loss of either melatonin or MT1 receptors results in an age related decline in ganglion cell numbers and an increase in intra-ocular pressure (Alcantara-Contreras et al, 2011, Baba et al, 2009).…”
Section: Retinal Clock and Eye Diseasementioning
confidence: 99%
“…Such a result also indicates that MT 1 and MT 2 receptors form heterodimers in mouse photoreceptors (Baba et al, ). Further studies have also demonstrated that removal of MT receptors in addition affects the viability of the photoreceptors and retinal ganglion cells during aging (Baba et al, ; Alcantara‐Contreras et al, ; Gianesini et al, ) as well as corneal biology (Baba et al, ).…”
Section: Introductionmentioning
confidence: 99%